Problems of the Merdeka Curriculum Policy in Efforts to Improve the Academic Quality of Students at SMPN - Bahri, Syaiful; Yanto, Murni; Pratiwi, Dinar Putri (Indonesian Journal of Pedagogy and Teacher Education, 2024)
An educational concept known as the Independent Curriculum allows schools more latitude in creating curriculum that meet the requirements of their communities. The goal of this policy is to raise the academic caliber of SMPN students, however there are several obstacles in the way of its execution. Information gathered and acquired by library research. This article analyzes a few of the major obstacles encountered while attempting to raise SMPN students' academic standards. The issues with the autonomous curriculum policy in attempts to raise SMPN students' academic standards are the research's results. These challenges involve differences in quality between schools, difficulties in maintaining consistent educational standards, the readiness of teachers and stakeholders, as well as the need for proper evaluation and monitoring. appropriate. Apart from that, the involvement of parents and other stakeholders as well as an emphasis on local skills are also important aspects in overcoming these problems. This article provides a holistic picture of the condition of the Merdeka Curriculum in the context of efforts to improve academic quality in junior secondary schools, with the hope of contributing to further understanding of the dynamics and improvement of educational policies at the junior secondary school level.